Community Compliance in Implementing Health Protocols in Polma Village, Kulawi District, Sigi Regency - Rasyika Nurul Fadjriah; Arwan; Melan Susanti; Sadli Syam (Journal of Health and Nutrition Research, 2023)
The pandemic of Covid-19 has become a global problem and a threat to general public health. Sigi Regency is a moderate risk area with an incidence rate of 3,567 confirmed positive patients and a death rate reaching 111 people; Covid data in Kulawi District shows 171 people, particularly in Polma Village, reached 16 people. This research aimed to determine the description of community compliance in the application of health protocols in Polma Village, Kulawi District, Sigi Regency. This was qualitative research with a case study approach. Community compliance with mask-wearing is lacking due to feelings of claustrophobia, forgetfulness, neglect, and limited availability. Handwashing compliance is also low due to limited facilities and people ignoring them. Compliance with social distancing is lacking because it's not a familiar habit and is sometimes neglected. Compliance with avoiding crowds is lacking due to cultural obligations. However, compliance with reduced mobility has improved due to essential needs and compliance with health protocols